The human side of public organizations: contributions to organizational performance - O'Toole, Laurence J., Jr.; Meier, Kenneth J. (2009)
Researchers in recent years have focused systematically on whether public management matters in the performance of public organizations. Internal management of organizations' human capital is one such managerial function, and a growing literature argues for its importance in delivering results. A management-and-performance model available in the literature suggests an approach to test empirically for this relationship. Here evidence from hundreds of public organizations over a 4-year period is assembled toward that end. Even when a number of other aspects of management are included, the management of human capital is related positively to virtually all performance indicators. The findings validate arguments in the recent literature of the field and emphasize the importance for performance of public organizations' investing in their people. - Reproduced.
Keywords: Public education; Public administration; Organizations